Analysis of Deradicalisation Strategies Through Family Programmes in Indonesia - Godlif Sianipar; Hasmia Wahyunisa; Rizqa Febry Ayu; Mawaddatul Ulfa; M. Aguswal Fajri (Jurnal Pelita Raya, 2025)
This study develops a new paradigm of deradicalisation that positions the family as the leading actor, rather than merely the object of policy. Through the integration of a multidisciplinary approach and multi-stakeholder engagement, this study seeks to formulate a deradicalisation strategy that not only addresses the surface symptoms of radicalism but also the socio-cultural, psychological, and structural roots that drive it. This study applies a library research method, integrating key theories and empirical findings from multiple disciplines to gain a comprehensive understanding of family-based deradicalisation strategies in Indonesia. The results confirm that deradicalisation strategies through family programmes in Indonesia are a fundamental approach, but cannot be separated from the dynamics of internal conflict, generational change, and increasingly complex digital and social challenges. The family can indeed be an initial filter and strategic space in preventing radicalism, but its effectiveness depends heavily on its capacity for dialogue, digital literacy, and adaptability to changing times, as well as tangible support from the state and communities that strengthen the surrounding social ecosystem. State intervention in the private sphere of the family must be carried out sensitively and participatively, not through repressive surveillance, but through empowerment and facilitation of critical discussion spaces that build family resilience without sacrificing its autonomy.